Studi Penilaian Kinerja Sistem Irigasi Menggunakan Aplikasi Epaksi dan Metode Fuzzy Set Theory di Daerah Irigasi (DI) Ketapang Barat Kabupaten Sampang - Inadhi, Kania Laksita; Prayogo, Tri Budi; Fidari, Jadfan Shidqi (Fakultas Teknik, Universitas Brawijaya, 2022)
The region of Irigasi Ketapang Barat's system of Irigasi doesn't work as expected. The reason why this happened was because there were some problems, both technical and non-technical. Teknis problems are caused by a lot of sediment, but for non-technical problems, there aren't any people around when the air is coming in. It's important to figure out how the system works to solve this problem. In this case, fuzzy set theory and applications of epaksi are used to figure out how well a system works. What from the two methods above will be compared and uji hipotesis will be done. To figure out what needs to be done first, use the PSTEK tool (Profi, Sosial, Teknik, Ekonomi, dan Kelembagaan).